2022
DOI: 10.7759/cureus.21773
|View full text |Cite
|
Sign up to set email alerts
|

Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis: What We Already Know

Abstract: Acute pancreatitis is the most common serious complication of endoscopic retrograde cholangiopancreatography (ERCP) resulting in significant morbidity and occasional mortality. Post-ERCP pancreatitis (PEP) has been recognized since ERCP was first performed, and many studies have shown a consistent risk that must be balanced against the many benefits of this procedure. This review will discuss the pathogenesis, epidemiology, potential risk factors, and clinical presentation of PEP. Moreover, it will discuss in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…However, the exact timing and concentration of serum amylase raises are unknown (22). It has been suggested that a dynamic rise of serum amylase between 3 and 6 hours after ERCP can be diagnostic of PEP (1). We measured the amylase level 6 h after doing ERCP in this trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact timing and concentration of serum amylase raises are unknown (22). It has been suggested that a dynamic rise of serum amylase between 3 and 6 hours after ERCP can be diagnostic of PEP (1). We measured the amylase level 6 h after doing ERCP in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography (ERCP) is an advanced procedure used for both diagnosis and therapeutic objectives in patients with pancreaticobiliary disorders (1). Although it is a difficult technique that requires specialized training, the use of ERCP appears to be increasing with time (2).…”
Section: Introductionmentioning
confidence: 99%
“…Post-ERCP pancreatitis (PEP) is the most prevalent and serious ERCP-associated complication, with an incidence that ranges between 3% and 5% in low-risk patients and as high as 15% in high-risk patients [1][2][3][4]. ERCP induces pancreatic injury and inflammation in two main mechanisms: mechanical damage from instrument handling and hydrostatic compression damage from contrast media [5,6]. There are many ERCP procedures involving prolonged instrument operation of the pancreatic duct, such as long-term or repeated pancreatic intubation, which can cause direct injury to the pancreatic duct or ampulla.…”
Section: Introductionmentioning
confidence: 99%
“…There are many ERCP procedures involving prolonged instrument operation of the pancreatic duct, such as long-term or repeated pancreatic intubation, which can cause direct injury to the pancreatic duct or ampulla. In addition, some procedures operated by an electric knife can result in mechanical and thermal injury, subsequently lead to secondary trypsin injury after reactive edema and obstruction of the pancreatic duct [5]. The pancreatic injury induced by contrast mainly includes hydrostatic compression damaged by overuse of contrast or chemical or allergic damage induced by contrast [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation